Metformin inhibits the proliferation of hepatocellular carcinoma cells through inducing ferroptosis analyzed by phosphoproteomics - Sun, Jihan; Yu, Xi; Shan, Yuying; Dai, Manyun; Gaucherot, Andrea; Lu, Caide; Mao, Shuqi (Frontiers in Oncology, 2025)
IntroductionThis study aims to investigate the effects of Metformin on hepatocellular carcinoma cell lines, cell lines and explores the molecular mechanisms underlying.MethodsBel-7402 and HepG2 cells were treated with varying concentrations of Metformin and ferrostatin-1 to assess cytotoxicity using the MTT assay. Protein expression and phosphorylation changes were analyzed through a phosphoproteomics approach and further bioinformatics analysis, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. The data from phosphoproteomics were confirmed by western blot. Metformin treatment significantly reduced cell viability in a concentration- and time-dependent manner. Phosphoproteomics analysis identified differentially expressed proteins (DEPs) primarily associated with ferroptosis and cellular metabolism. Further GO and KEGG analyses revealed the involvement of DEPs in nucleotide biosynthesis, membrane transport, and metabolic pathways. Then the bioinformatic data were verified through MTT and western blot.Results and discussionThe results showed that ferrostatin-1 could partly reverse the inhibitory effects of Metformin, suggesting the involvement of ferroptosis. Moreover, the modulation of autophagy and ferroptosis-related proteins by Metformin was confirmed by western blot. Our findings demonstrate that Metformin induces ferroptosis in Bel-7402 and HepG2 cell lines, potentially offering a novel therapeutic strategy for the treatment of hepatocellular carcinoma. The phosphoproteomics analysis provides insights into the molecular mechanisms by which Metformin exerts its anti-cancer effects.